Как свежи были розы в аду: роман / Евгения Михайлова - Михайлова Евгения (Детектив-событие, 2012)
Экземпляры: (20220419) / Инвентарный номер: 36658 / Цена: 708.40 / Сис.шифр: 84(2=411.2)6 / Авт.знак: М 69 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6